EXOGENOUS APPLICATION OF TRYPTOPHAN AND INDOLE ACETIC ACID (IAA) TO INDUCE ROOT NODULE FORMATION AND INCREASE SOYBEAN YIELD IN ACID, NEUTRAL AND ALKALINE SOIL - Sudadi, Sudadi; Suryono, Suryono (Faculty of Agriculture University of Brawijaya in collaboration with PERAGI, 2015)
The research aimed to study whether soil pH affects exogenous application of amino acid tryptophan and IAA in increasing root nodules and soybean yield. The experiment was conducted in greenhouse using 20 cm diameter plastic pot filled with fine soil, arranged in completely randomized design (CRD) with four treatments. Each treatment combination was repeated three times. Three seeds of local soybean variety were planted into each pot then to remain one plant a week after planting. Variables observed were root nodules number, shoot dry weight and seed yield. Plant nutrients were supplied in the form of solution to meet crop needs. The data obtained were analyzed statistically by F test at 5% of level confidence, followed by Duncan's multiple range test when there was a significant effect. The results showed that both exogenous amino acid tryptophan and IAA increased number of root nodules, shoot and root dry weight and soybean yield. Higher root nodules number was taken from the treatment combination of 0.001 ppm IAA applied at V3 in Alfisol and Vertisols, and 1.0 ppm on Entisols. However, the highest soybean yields were taken from the treatment combination of 1.0 ppm tryptophan applied at V0 in Alfisols (6.51 g plant-1).